2018
DOI: 10.1021/acscatal.8b00106
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of Active Site Structures with Improved Transition-State Scaling for Ammonia Synthesis

Abstract: The Haber–Bosch process for the reduction of atmospheric nitrogen to ammonia is one of the most optimized heterogeneous catalytic reactions, but there are aspects of the industrial process that remain less than ideal. It has been shown that the activity of metal catalysts is limited by a Brønsted–Evans–Polanyi (BEP) scaling relationship between the reaction and transition-state energies for N2 dissociation, leading to a negligible production rate at ambient conditions and a modest rate under harsh conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 36 publications
(64 reference statements)
4
106
0
Order By: Relevance
“…The most insightful theoretical studies in the NRR context, from our perspective, are those that build upon the theory in the first place. This can be either an overarching analysis of the general trends, plausible mechanisms and key limiting steps for the NRR catalysed by a broad family of materials 2,[40][41][42][43] , or a more specific investigation of one particular highly promising system [44][45][46][47][48] . Ideally, this kind of theoretical work should be followed by experiments to confirm the predicted activity, though unfortunately, we are not aware of any NRR work that has successfully followed that pathway.…”
Section: Understanding Nrr Through Computational Chemistrymentioning
confidence: 99%
“…The most insightful theoretical studies in the NRR context, from our perspective, are those that build upon the theory in the first place. This can be either an overarching analysis of the general trends, plausible mechanisms and key limiting steps for the NRR catalysed by a broad family of materials 2,[40][41][42][43] , or a more specific investigation of one particular highly promising system [44][45][46][47][48] . Ideally, this kind of theoretical work should be followed by experiments to confirm the predicted activity, though unfortunately, we are not aware of any NRR work that has successfully followed that pathway.…”
Section: Understanding Nrr Through Computational Chemistrymentioning
confidence: 99%
“…For example, Choi et al indicated that NRR selectivity on single metal sites is significantly higher than that on bulk metals surfaces due to the effective suppression of the HER with the help of ensemble effect . Nørskov and co‐workers found that “on top” binding of nitrogen that is possible on single metal sites can enhance the rate of NH 3 synthesis . Moreover, it has been found that N species can promote the dissociation of N 2 , especially in the presence of single‐metal Lewis acid ions .…”
Section: Introductionmentioning
confidence: 99%
“…The use of a simple metal catalyst opens the probability of understanding the complex interactions of catalyst and plasma experimentally by studying the point-emission spectra at the metal plasma interface. Pure transition metals have been quite widely studied using molecular simulation for ammonia synthesis [25,26]. However, a novel class of metals and alloys known as low-melting point alloys has been ignored for catalytic applications in experimental as well as simulation reports.…”
Section: Introductionmentioning
confidence: 99%